KONGRUENSI PADA SEMIALJABAR ATAS HEMIRING - SaniMusyafa Hikam; Bambang Irawanto (Jurnal Matematika, 2012)
A hemiringR is called S -semialgebra if R is a left and right semi module over S satisfying axb=a(xb) for all a,b ∈S and x∈R . On the S -semialgebra R can be defined a congruence. A congruence on the S -semialgebra R is any congruence on the hemiring R which is both a left and right compatible for any multiplication by element of S . Therefore, the properties of congruence on a hemiring can be  generalized to congruence on a semi algebra over a hemiring